A Study on Parameterization of the Beijing Winter Heavy Haze Events Associated with Height of Pollution Mixing Layer - Tao Niu; Jizhi Wang; Yuanqin Yang; Yaqiang Wang; Cheng Chen (Advances in Meteorology)
North China Plain, Beijing, Tianjin, and Hebei province are the major areas facing the decreasing air quality and frequent pollution events in the recent years. Identifying the effect of meteorological conditions on changes in aerosol concentration and the mechanism for forming such heavy pollution in North China Plain has become the focus of scientific research. The influence of atmospheric boundary layer characteristics on air quality has become the focus of attention and research. However, the boundary layer describes that the influences of air pollution have sometimes been duplicated and confused with each other in some of the studies. It is necessary to pay attention to some extent, raising awareness of related pollution mixing layer. The conclusions of the study include the following: (1) The lowered height of pollution mixing layer (H_PML) was favorable for the increase of the PM2.5 density. The lowered height of pollution mixing layer had significant impacts on formation of severe haze. (2) A statistical analysis of large-scale heavy pollution cases in eastern China shows that the H_PML parameters have significant contributions. (3) The feedback effect of the high value of the convection inhibition (CIN), which is unfavorable to vertical diffusion of pollution, causes further reduction of H_PML, resulting in cumulative pollution again.